2014
DOI: 10.1128/aem.01296-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mn(II)-Oxidizing Bacteria from a Low-pH Contaminated Former Uranium Mine

Abstract: e Biological Mn oxidation is responsible for producing highly reactive and abundant Mn oxide phases in the environment that can mitigate metal contamination. However, little is known about Mn oxidation in low-pH environments, where metal contamination often is a problem as the result of mining activities. We isolated two Mn(II)-oxidizing bacteria (MOB) at pH 5.5 (Duganella isolate AB_14 and Albidiferax isolate TB-2) and nine strains at pH 7 from a former uranium mining site. Isolate TB-2 may contribute to Mn o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 55 publications
(76 reference statements)
2
36
0
Order By: Relevance
“…Whereas previous studies have demonstrated pH dependence of both fungal (Miyata et al ., ) and bacterial (Zhang et al ., ; Akob et al ., ) Mn(II) oxidation, our current study highlights the importance of the availability of carbon and other nutrients as important drivers of Mn(II) oxidation in environments such as caves. In addition, we show that microbial community composition and abundance can be intricately linked with the quality, quantity and form of the carbon input.…”
Section: Discussionmentioning
confidence: 68%
“…Whereas previous studies have demonstrated pH dependence of both fungal (Miyata et al ., ) and bacterial (Zhang et al ., ; Akob et al ., ) Mn(II) oxidation, our current study highlights the importance of the availability of carbon and other nutrients as important drivers of Mn(II) oxidation in environments such as caves. In addition, we show that microbial community composition and abundance can be intricately linked with the quality, quantity and form of the carbon input.…”
Section: Discussionmentioning
confidence: 68%
“…Natural attenuation of trace metal loads commonly occurs via a complex set of processes (Akob et al, 2014;Byrne et al, 2014;De Giudici et al, 2009, 2014Fuller and Bargar, 2014) Root growth enhances soil permeability with the development of a macropore system called rhizopores (Archer et al, 2013;Ghestem et al, 2011). As reviewed by Vergani and Graf (2015), the overall effect of plants on soil permeability depends on the soil type, the density of vegetation and the vegetation cover type.…”
Section: Vegetation Hydrology Hyporheic Zone and Biogeochemical Barmentioning
confidence: 99%
“…The pH of environments that would be good targets for Mn oxide-mediated attenuation, e.g., drainage basins, mine tailings, and leaching heaps, is normally acidic due to the aerobic oxidation of sulfidic minerals (3). Although manganese is readily oxidized from Mn(II) to Mn(III/IV) at circumneutral pH by a variety of microorganisms (4), we have limited knowledge about the formation of biogenic Mn oxides in acidic environments (5,6).…”
mentioning
confidence: 99%
“…In contrast, low-pH Mn(II) oxidation poses a challenge to microbes because the reaction is thermodynamically unfavored (5,6,19,20). Until recently, only the fungus Cephalosportium sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation